Impulse buying pada pengunjung pusat pembelanjaan dan faktor yang mempengaruhi - Irwan Misbach (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, Indonesia, 2022)
This study aims to determine the factors that influence consumers to make impulse purchases at malls visitors. The independent variables studied were; service quality, product display, price, promotion, hedonic shopping value, and impulsive purchases of mall visitors in Makassar City as the dependent variable. This is an associative quantitative study, the samples were taken by accident and the data were analyzed using Multiple Linear Regression, t-test & f-test. The results of the study prove that the quality of service and product appearance has a negative and significant effect on impulse buying, while the price, promotion, and hedonic shopping value factors have a positive and significant effect on impulsive buying at Mall visitors. Variables of price, promotion, and value of hedonic shopping are theoretical implications of the factors that influence impulse buying. The practical consequence is that companies in increasing profit potential pay more attention to these variables.